Computational Approach for Human Bioenergy Field Imaging and Analysis for Human Wellness - CHHABRA, GUNJAN; PRASAD, AJAY; MARRIBOYINA, VENKATADRI (International Journal of Psychosocial Rehabilitation, 2020)
Complementary and Alternative Medicine (CAM) researchers’ committee stated a term called Biofield in 1994. The previous study shows the substantial evidence of its existence and its impact on the health and thought process of an individual. Due to the lack of its scientific documentation and examination, usage and belief of biofield in various domains are not very popular. The biofield is an extremely weak electromagnetic bio-information field, which is very hard to measure and visualize. It is a field of energy around every seen and unseen, living and non-living, holds a higher order of dynamic information within itself. CAM practitioners challenge that this bioenergy has mind-like properties reflecting ones’ physiological thought process, inner qualities, wellness, organ coordination, and others. Due to its invisibility (through naked eyes) and weak strength, scientific measurements, analysis and belief of its existence is questionable. This research article highlights a method for the visualization, analysis, and medical benefits of biofield measurement. Current research also highlights the applications of biofield study in the future, i.e., and its further study will open up new gateways for investigation and bring remarkable changes in society.